Comments to the legislative definition of “transport security”. (Journal of actual problems of jurisprudence, 2016)
Basic elements of transport security within the framework of legislative concepts are revealed in the article. The most important among them are national interests in the field of transport, transport security threats, measures of counteraction to the threats of transport security. The distinctive features of the modern mechanism of legislative regulation in transport security of Kazakhstan are formulated on the basis of this research.
Keywords: transport safety; national interests in the field of transport; transport security threats; counteraction to transport security threats